2012
DOI: 10.1371/journal.pgen.1002854
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in REC8, RNF212, and PRDM9 Influence Male Recombination in Cattle

Abstract: We use >250,000 cross-over events identified in >10,000 bovine sperm cells to perform an extensive characterization of meiotic recombination in male cattle. We map Quantitative Trait Loci (QTL) influencing genome-wide recombination rate, genome-wide hotspot usage, and locus-specific recombination rate. We fine-map three QTL and present strong evidence that genetic variants in REC8 and RNF212 influence genome-wide recombination rate, while genetic variants in PRDM9 influence genome-wide hotspot usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
157
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(177 citation statements)
references
References 49 publications
17
157
3
Order By: Relevance
“…The BTA10 (21.23 Mb) QTL was previously attributed to variants in the REC8 gene (Sandor et al 2012). Sequence-based finemapping performed in this study indicates that the association maximizes at 645 kb from REC8.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…The BTA10 (21.23 Mb) QTL was previously attributed to variants in the REC8 gene (Sandor et al 2012). Sequence-based finemapping performed in this study indicates that the association maximizes at 645 kb from REC8.…”
Section: Discussionsupporting
confidence: 50%
“…S30). It is noteworthy that we previously showed that coding variants in an X-linked PRDM9 paralog (with highest similarity to the human PRDM9 gene) strongly affect hotspot usage in males (Sandor et al 2012), but this was not confirmed by Ma et al (2015). Combined with the observation of limited sharing of recombination hotspots between males and females (Ma et al 2015), these observations suggest that hotspot usage may be differentially regulated in both sexes in cattle.…”
Section: −12mentioning
confidence: 71%
See 2 more Smart Citations
“…As HEI10 belongs to a conserved gene family, which encodes RING domain SUMO/ubiquitin E3 ligases that promote crossovers in diverse eukaryotes, this was the strongest candidate gene for rQTL1 (Supplemental Figs. S2, S3;Bhalla et al 2008;Kong et al 2008;FledelAlon et al 2011;Chelysheva et al 2012;Sandor et al 2012;Serrentino et al 2013;De Muyt et al 2014;Qiao et al 2014;Johnston et al 2016;Rao et al 2017). HEI10 family proteins possess N-terminal RING domains, central coiled-coil domains, and C-terminal regions of unknown function (Supplemental Figs.…”
Section: Genetic Mapping Of Arabidopsis Recombination Quantitative Trmentioning
confidence: 99%